Enrichment of antiâ€ulcer activity of monoammonium glycerrhizin and Aloe vera gel powder through a novel drug delivery system - Ranade, Mrs. Arati N. (Asian Journal of Pharmaceutics (AJP), 2014)
Usual treatment for Helicobacter pyloriâ€induced peptic ulcer includes a 14â€day â€œtriple therapyâ€ of two antibiotics and a proton pump inhibitor. However, the current therapy has sideâ€effects like stomach upset, nonâ€compliance, incompleteÂ absorption of drug and antibiotic resistance. To overcome these limitations, there is a need to suggest an alternative therapy.Â The best possible alternative is to deliver herbal constituents. The purpose of the present study was to optimize the efficacyÂ of herbal constituents by applying the concept of a novel drug delivery system.The present investigation is designed to deliverÂ and retain two herbal constituents in the stomach for better action against gastric ulcers. The objective was to develop aÂ bilayer floating tablet of monoammonium glycerrhizin and Aloe vera gel powder through rational combination of excipientsÂ to give the lowest possible lag time with maximum drug release in 7 h. Formulation OF2 containing hydroxy propyl methylÂ cellulose E5, crospovidone and effervescent agents in the ratio 1:2 gave 98% drug release with desired floating properties.Â Pharmacodynamic studies in rats showed that the combination of monoammonium glycerrhizin and Aloe vera gave 99%Â ulcer inhibition in comparison with 51% ulcer inhibition in the group administered with monoammonium glycerrhizinÂ alone. Xâ€ray studies in rabbits proved the gastroretention of the tablet for more than 6 h. This suggests relevance of NDDSÂ in delivery of herbal constituents in the treatment of gastric ulcer. Key words: Aloe vera, floating tablet, gastric ulcer, monoammonium glycerrhizin, pharmacodynamic studies